Place navigation in the Morris water maze under minimum and redundant extra-maze cue conditions - Fenton, A A; Arolfo, M P; Nerad, L; Bures, J (Behavioral and neural biology, 1994)
Complex relational processes underlying place navigation learning were analyzed by minimizing the relational elements available to rats. The animals navigated in a standard water maze in darkness using controlled remote visual cues (back-lit shapes in opaque buckets aimed at the pool to keep the background dark) while being tracked by an infrared camera and computer. Learning was similar with 2 (AB) or 4 (ABCD) cues and as good as in a fully lit room with many cues (asymptotic escape time t = 5-7 s). The ABCD-trained rats were not impaired by removal of any 2 cues (t = 7). For AB-trained rats, adding 2 new cues (ABEF) or replacing AB with EF (EF) caused small (t = 11) or big disruptions (t = 20), respectively. By block 2, both groups (ABEF, EF) returned to asymptotic performance. But testing the ABEF rats on block 2 with only EF indicated that EF was learned (t = 12) but not as well as when only EF was present (t = 5). Thus transfer from a redundant to a minimal cue condition is immediate and easier than vice versa. Theoretical implications are discussed.
Keywords: Escape Reaction; přenos učení (psychologie); pozornost; Retention, Psychology; Cues; rozpomínání; Orientation; úniková reakce; Attention; Transfer, Psychology; lidé; orientace; retence (psychologie); Association Learning; Mental Recall; Visual Perception; diskriminační učení; podněty; zraková percepce; Male; asociační učení; Maze Learning; mužské pohlaví; bludiště - učení; Discrimination Learning; Humans